2023
DOI: 10.3390/vetsci10020113
|View full text |Cite
|
Sign up to set email alerts
|

Image Classification and Automated Machine Learning to Classify Lung Pathologies in Deceased Feedlot Cattle

Abstract: Bovine respiratory disease (BRD) and acute interstitial pneumonia (AIP) are the main reported respiratory syndromes (RSs) causing significant morbidity and mortality in feedlot cattle. Recently, bronchopneumonia with an interstitial pattern (BIP) was described as a concerning emerging feedlot lung disease. Necropsies are imperative to assist lung disease diagnosis and pinpoint feedlot management sectors that require improvement. However, necropsies can be logistically challenging due to location and veterinari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These models are trained on images of necropsied right lateral lungs annotated with gross diagnoses. Although they have demonstrated moderate sensitivity in detecting BRD, there is a need for further refinement to enhance their diagnostic accuracy [123].…”
Section: Necropsy As a Brd Gold Standard Diagnostic Testmentioning
confidence: 99%
“…These models are trained on images of necropsied right lateral lungs annotated with gross diagnoses. Although they have demonstrated moderate sensitivity in detecting BRD, there is a need for further refinement to enhance their diagnostic accuracy [123].…”
Section: Necropsy As a Brd Gold Standard Diagnostic Testmentioning
confidence: 99%
“…An animal could also have been treated at least one time for AIP or BP and at least one time for OTHER diagnoses (BP or AIP + OTHER). At treatment, 13.2% (47) of the animals were diagnosed with AIP, 34.5% (123) with BP, 5% (18) with AIP + BIP, 10.6% (38) with BP or AIP + OTHER, 9.5% (34) with OTHER, and 27.2% (97) were not diagnosed or treated while alive. When comparing the diagnoses found at necropsy with the feedyard diagnoses, AIP had an agreement of 22.5% and a Cohen's kappa of 0.098 (Figure 1).…”
Section: Necropsy Gross Diagnoses and Feedyard Diagnosismentioning
confidence: 99%
“…Recently, researchers reported the simultaneous presence of AIP and BP in deceased feedyard cattle. A new classification has been suggested as bronchopneumonia with an interstitial pneumonia (BIP) due to the presence of lesions compatible with AIP in caudodorsal lobes and BP on cranioventral lobes [ 16 , 17 , 18 , 19 ]. In previous studies when lesions consistent with BIP were found during necropsy, the final diagnosis or cause of death was limited to AIP or BP only, and it was dependent on the pathology that affected the majority of the lung [ 14 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The utmost generally used image techniques are CT, and CXR imaging. These are analytical tools in allowing physicians to look at the internal structure of the human body by not involving surgery [5]. Discovering pulmonary ailment is presently accomplished by a professional radiologist through CXR image inspection because of its non-invasive valuation and comfort for total discoveries of the chest conditions in short.…”
Section: Introductionmentioning
confidence: 99%